The pattern of anthrax cases on livestock in West Nusa Tenggara Province - Enymartindah .; S Wahyuwardani (Jurnal Ilmu Ternak dan Veteriner, 1998)
A retrospective study on anthrax in endemic area was carried out from 1984 to 1994 in West Nusa Tenggara Province (NTB) to uncover the occurrence of anthrax and the pattern of the disease in livestock. Data of anthrax incidence had been compiled for the 11 years from Animal Health Section and Type B Laboratory of the Livestock Service Office, NTB Province in Mataram. This was done to get the information about locations and times when the cases occurred, and the vaccination status of livestock in the anthrax area. The pattern of anthrax in livestock was analyzed by using time series analysis, and the long term trend was then illustrated by linier regression . During the years, anthrax cases in livestock were reported high in Sumbawa island, while the cases in Lombok island were relatively low. There were no anthrax cases reported from East Lombok District . The long term trend of anthrax occurrence in livestock from 1984 to 1994 tended to decrease (Y= 6,04 - 0,0162 X).   Keywords: Anthrax, cases pattern, retrospective study